2021
DOI: 10.30862/casssowary.cs.v4.i2.79
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kualitas Air Lindi dan Permukaan pada areal TPA Sowi Gunung dan Sekitarnya di Kabupaten Manokwari Papua Barat

Abstract: The aim of the research was to determine the quality of leachate water in the processing unit (IPAL) of TPA Sowi Gunung and the quality of surface water around the TPA in relation to the operation of the IPAL TPA.The method used in this research is descriptive method with cross sectional survey technique by collecting leachate samples from the IPAL unit and surface water samples from two springs around the landfill area accompanied by in situ measurements of pH parameters and continued with 6 parameter quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…Garbage that continues accumulating will cause methane fermentation due to anaerobic biological decomposition, which causes the pH to become alkaline (Angrianto et al, 2021). Vidyawati and Fitrihidajati (2019) showed that using WH as a phytoremediation agent could neutralise the pH of tofu liquid waste from 4.21 to 7.34.…”
Section: Discussionmentioning
confidence: 99%
“…Garbage that continues accumulating will cause methane fermentation due to anaerobic biological decomposition, which causes the pH to become alkaline (Angrianto et al, 2021). Vidyawati and Fitrihidajati (2019) showed that using WH as a phytoremediation agent could neutralise the pH of tofu liquid waste from 4.21 to 7.34.…”
Section: Discussionmentioning
confidence: 99%
“…The increased acid production and decreased pH due to rapid biodegradation increased the ability of water to dissolve waste components. This situation is compounded by the infiltration of runoff water and human waste [21,22]. High BOD and COD values indicate high water pollution caused by organic matter [3].…”
Section: Initial Leachate Characteristicsmentioning
confidence: 99%
“…Total-Nitrogen merupakan ikatan dari nitrat (NO 3-), nitrit (NO 2-), dan amonia (NH3). Nitrogen adalah faktor penting yang ada dalam sistem biologi setiap makhluk hidup (Angrianto et al, 2021). Terdapat beberapa pengolahan dalam air lindi seperti pengolahan fisika antara lain membran filtrasi, evaporasi, dan juga pertukaran ion.…”
Section: Pendahuluanunclassified